Dinamika Formalisasi Syariat Islam di Indonesia - Kurniawan Kurniawan (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: The purpose of this study was to describe a long struggle to incorporate Islamic law into the constitution and various legislations in Indonesia pre and post Indonesia’s Independence. In addition, this study also illustrates the challenges faced by Moslems who brought the idea of formalization and implementation of Islamic law into state institutions as well as regional institutions such as the Aceh region. The study also tried to give an idea how far the opportunities provided by democracy in Indonesia at this time to be used by the Muslims to offer what they consider as the Islamic law. The research was done by using library research (normative research) through collecting and studying literatures, legislations, law journals, encyclopedias, as well as citing the opinions of scholars and activists (human defender) Islamic law and other relevant opinion. Therefore this type of study called normative legal research or study by using a conceptual analysis of social history and law issue (legal-historical social approaches). The study result shows that the efforts made by Moslem people to get guarantee constitutionally in implementing Islamic, essentially has got a great opportunity in line with the basic legitimating granted by Article 29 of the 1945 Constitution. In the current era of democracy, there are some opportunity to synchronize elements of Islamic law into policies and legislations products is a major challenge, especially for areas that are socially and culturally not or not yet ready to apply them in daily life people. The Dynamics of Formalization of Islamic Law in Indonesia